Geoneutrinos - Ondřej Šrámek; William F. McDonough; John G. Learned (Advances in High Energy Physics)
Neutrino geophysics is an emerging interdisciplinary field with the potential to map the abundances and distribution of radiogenic heat sources in the continental crust and deep Earth. To date, data from two different experiments quantify the amount of Th and U in the Earth and begin to put constraints on radiogenic power in the Earth available for driving mantle convection and plate tectonics. New improved detectors are under construction or in planning stages. Critical testing of compositional models of the Earth requires integrating geoneutrino and geological observations. Such tests will lead to significant constraints on the absolute and relative abundances of U and Th in the continents. High radioactivity in continental crust puts limits on land-based observatories' capacity to resolve mantle models with current detection methods. Multiple-site measurement in oceanic areas away from continental crust and nuclear reactors offers the best potential to extract mantle information. Geophysics would benefit from directional detection and the detectability of electron antineutrinos from potassium decay.